Pilot Study Comparing Adverse Cardiorespiratory Events among Pharmacologically and Nonpharmacologically Treated Infants Undergoing Monitoring for Neonatal Abstinence Syndrome - Spoorthi Davala, BA; Aaron Hansbury, MPH; Melissa Miller, MPH; Jeffery Boateng, MPH; Hira Shrestha, MA; Elisha M. Wachman, MD (Elsevier, 2020)
There is variation in cardiorespiratory monitoring practices for neonatal abstinence syndrome. We examined the incidence of cardiorespiratory adverse events in infants with neonatal abstinence syndrome who were treated or nontreated pharmacologically. Eight (10%) in the nontreated and 23 (19%) in the treated group experienced adverse events. This warrants further investigation in a larger cohort.